A new species of Microlicia (Melastomataceae) from the Espinhaço Range, Minas Gerais, Brazil - Romero, Rosana (Phytotaxa, 2013)
A new endemic species of Microlicia from campos rupestres of the Espinhaço Range is described and illustrated. The new species is characterized by having leaves of different sizes distributed along the branches, petioles 1–2 mm long, leaf blade that are attenuate at the base, with an entire margins, prominent and thickened nerves mainly on the abaxial surface, and an indumentum of short pale, glandular trichomes and sessile golden glands covering the whole plant. It resembles M. avicularis, M. tomentella and M. elegans, which also occur in the Espinhaço Range, in Minas Gerais state.